2021
DOI: 10.1007/s40145-021-0461-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of CMAS resistant bixbyite structured high-entropy oxides RE2O3 (RE = Sm, Eu, Er, Lu, Y, and Yb): Promising environmental barrier coating materials for Al2O3f/Al2O3 composites

Abstract: Y2O3 is regarded as one of the potential environmental barrier coating (EBC) materials for Al2O3f/Al2O3 ceramic matrix composites owing to its high melting point and close thermal expansion coefficient to Al2O3. However, the relatively high thermal conductivity and unsatisfactory calcium-magnesium-aluminosilicate (CMAS) resistance are the main obstacles for the practical application of Y2O3. In order to reduce the thermal conductivity and increase the CMAS resistance, four cubic bixbyite structured high-entrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 63 publications
1
38
0
Order By: Relevance
“…The higher hardness and strength but comparable fracture toughness and Young's modulus imply that the high-entropy carbide [170] has become more brittle. The very recent work by Sun et al [176] clearly indicated that high-entropy bixbyite structured oxides RE 2 O 3 (RE = Sm, Eu, Er, Lu, Y, and Yb) had higher brittleness and lower damage tolerance values, implying that they are more brittle than the single component like Y 2 O 3 . Needless to say, more works are needed to confirm the brittleness of HECs.…”
Section: Hardness and Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher hardness and strength but comparable fracture toughness and Young's modulus imply that the high-entropy carbide [170] has become more brittle. The very recent work by Sun et al [176] clearly indicated that high-entropy bixbyite structured oxides RE 2 O 3 (RE = Sm, Eu, Er, Lu, Y, and Yb) had higher brittleness and lower damage tolerance values, implying that they are more brittle than the single component like Y 2 O 3 . Needless to say, more works are needed to confirm the brittleness of HECs.…”
Section: Hardness and Strengthmentioning
confidence: 99%
“…For structural applications, low fracture toughness and damage tolerance are the main limitations that must be overcome. Although the available data are very limited, recent work by Sun et al [176] indicates that high-entropy bixbyite-structured oxides RE 2 O 3 (RE = Sm, Eu, Er, Lu, Y, and Yb) are more brittle than the single component Y 2 O 3 , which needs further attention in the development of HECs. Actually, considering the enhanced hardness and strength instead of fracture toughness, high-entropy carbide (HfZrTiTaNb)C is also brittle albeit its strength can be maintained up to 1800 ℃ [170].…”
Section: Tuning Properties For Prospective Applicationsmentioning
confidence: 99%
“…Compared to YSZ, which is the most promising TBC materials, high‐entropy RE 2 (Y 0.2 Yb 0.2 Nb 0.2 Ta 0.2 Ce 0.2 ) 2 O 7 oxides exhibit similar TECs and much lower thermal conductivity, which make them distinct from the other promising TBC materials. [ 25,51–62 ] Figure 7B shows the XRD patterns of high‐entropy RE 2 (Y 0.2 Yb 0.2 Nb 0.2 Ta 0.2 Ce 0.2 ) 2 O 7 oxides after being treated at 1500°C for 50 h. It is obvious that there is no detectable phase decomposition or transformation can be observed, indicating the superior phase stability of high‐entropy RE 2 (Y 0.2 Yb 0.2 Nb 0.2 Ta 0.2 Ce 0.2 ) 2 O 7 oxides under high‐temperature and long‐term thermal exposure conditions.…”
Section: Resultsmentioning
confidence: 99%
“…(A) The thermal conductivity versus TECs for the high‐entropy RE 2 (Y 0.2 Yb 0.2 Nb 0.2 Ta 0.2 Ce 0.2 ) 2 O 7 oxides as well as other conventional TBC materials [ 25,51–62 ] ; (B) the phase stability of high‐entropy RE 2 (Y 0.2 Yb 0.2 Nb 0.2 Ta 0.2 Ce 0.2 ) 2 O 7 oxides after thermal exposure at 1500°C for 50 h. TECs, thermal expansion coefficients; TBC, thermal barrier coating…”
Section: Resultsmentioning
confidence: 99%
“…With the development of aeroengines, hot‐end components to resist high‐temperature environmental corrosion become more and more important. Fiber‐reinforced silicon carbide‐based ceramic composites (SiC‐CMC) have been considered the most promising candidate for next‐generation aircraft engine components due to their low density, high‐temperature resistance, excellent mechanical properties, oxidation, and corrosion resistance 1–4 . Benefitting by the good heat shield, SiC‐CMCs can be used at much higher temperature and require less cooling, which increases the efficiency, reduces emissions of the polluting gases such as CO 2 and NO x and, therefore, enable engines to run hotter and more efficiently at higher thrust 5,6 …”
Section: Introductionmentioning
confidence: 99%